Introduction to Wind Energy Systems Basics, Technology and Operation - Wagner, Hermann-Josef; Mathur, Jyotirmay (Green Energy and Technology, 2013)
In the past few decades, growth in the wind energy sector has been most phenomenal among all renewable energy resources. And, in this context, it is nearly universally agreed that wind energy can definitely play an important part in ensuring a sustainable future. The present book was written to address the needs of those readers interested in wind energy converters. The authors have tried to strike a balance between a short book chapter and a very detailed book for experts in the field. There were three prime reasons behind doing so: first, the field is highly interdisciplinary and requires a more accessible format for non-experts. The second reason for this more compact version is that both authors have encountered many students and technically oriented people who were searching for this type of book on wind energy. The third reason and motivation for writing this book was to provide some initial information to people who are embarking on a career in the wind industry. It is this group of people that the present book is targeted at.